Influence of Plantain Pseudostem Fibres and Lime on the Properties of Cement Mortar - Humphrey Danso (Advances in Materials Science and Engineering)
This study investigated the properties of cement mortar with lime reinforced with plantain pseudostem fibres. Experimental specimens with 0, 0.25, 0.5, 0.75, and 1% fibre contents by weight of sand and 10% lime content by weight of cement were prepared and tested on 7, 14, 21, and 28 days of curing for density, tensile strength, compressive strength, SEM, and EDS. The 0.25% plantain pseudostem fibre reinforced mortar achieved 23.4% compressive strength improvement over unreinforced mortar specimens. There was between 6.89 and 13.80% increase in tensile strength of the plantain pseudostem fibre reinforced mortar over the unreinforced mortar specimens. A positive linear correlation was found between the compressive strength and tensile strength of cement mortar reinforced with plantain pseudostem fibres and lime with coefficient of determinant (R2) values between 0.909 and 0.869. It was also observed that the plantain pseudostem fibre reinforced mortar specimen had some microcracks and voids from the SEM analysis. Furthermore, EDS analysis showed the presence of calcium silicate hydrate with a Ca/Si ratio of between 1.02 and 2.49, and Al/Si ratio of between 0.76 and 0.81 as the main oxide. It therefore concluded that the incorporation of plantain pseudostem fibre and lime positively influenced the properties of the cement mortar with the 0.25% fibre content being recommended for construction application.